Preparation, Investigation and Theoretical Study of α-chloroacetamide-N-(p-substituted) phenyl (Journal of Scientific Research, 2009)
Six new compounds of α-chloroacetamide-N-(p-substituted) phenyl of general formula ClCH2CONHPhX; where X = H,  Me,  OMe,  Br,  Cl  and NO2 have been prepared and investigated spectroscopically and theoretically.  AM1 and PM3 semi empirical methods were confirmed that compounds existed as amide form. Keywords: IR; 13CNMR; α-chloroacetamide-(N-P-X) phenyl; Correlation analysis; AM1 semi-empirical calculation.© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2301                 J. Sci. Res. 1 (3), 576-582 (2009)